2017
DOI: 10.1371/journal.pone.0186558
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of different air filter types for pig facilities at laboratory scale

Abstract: Air filtration has been shown to be efficient in reducing pathogen burden in circulating air. We determined at laboratory scale the retention efficiency of different air filter types either composed of a prefilter (EU class G4) and a secondary fiberglass filter (EU class F9) or consisting of a filter mat (EU class M6 and F8-9). Four filter prototypes were tested for their capability to remove aerosol containing equine arteritis virus (EAV), porcine reproductive and respiratory syndrome virus (PRRSV), bovine en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…We further chose PRRSV and Ungulate protoparvovirus I (formerly known as porcine parvovirus, PPV) because of their high economic impact in swine industry [2527]. Culture conditions and preparation of test suspensions for the bacteria and PRRSV has been previously described in detail [6]. Briefly, bacterial test suspensions in tryptic soy broth (Carl Roth GmbH + Co. KG, Karlsruhe, Germany) were adjusted to 10 8 −10 9 colony-forming units (cfu)/ml and PRRSV suspensions grown in MARC-145 cells revealed a titer of 10 5.6 –10 6.1 tissue culture infectious dose (TCID) 50 /ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further chose PRRSV and Ungulate protoparvovirus I (formerly known as porcine parvovirus, PPV) because of their high economic impact in swine industry [2527]. Culture conditions and preparation of test suspensions for the bacteria and PRRSV has been previously described in detail [6]. Briefly, bacterial test suspensions in tryptic soy broth (Carl Roth GmbH + Co. KG, Karlsruhe, Germany) were adjusted to 10 8 −10 9 colony-forming units (cfu)/ml and PRRSV suspensions grown in MARC-145 cells revealed a titer of 10 5.6 –10 6.1 tissue culture infectious dose (TCID) 50 /ml.…”
Section: Methodsmentioning
confidence: 99%
“…for porcine reproductive and respiratory syndrome virus (PRRSV), Foot-and-Mouth-Disease virus, Coxiella burnetii and Mycoplasma hyopneumoniae which can be transported over several kilometers by wind [1–5]. At laboratory scale, a reduction efficiency of 92% to 99.9% was demonstrated depending on the air-filter type and the viruses or bacteria used for testing [6]. Nevertheless, air filtration is still not commonly used in pig production although it minimizes the risk of introducing airborne pathogens by supply air [5–8] and can be used to reduce pathogen burden from indoor air by recirculating air filtration [913].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, indoor air quality can also be improved by filtering dust and its associated hazards. A high filtering efficacy (92.0%-99.9%) was demonstrated using two different air filter types for PRRSV, Staphylococcus aureus and Actinobacillus pleuropneumoniae at laboratory scale [ 22 ]. Filters consisted either of an EU class F9 (MERV 16) fiberglass filter combined to an upstream prefilter (EU class G4, MERV 6–8), or of a glass wool filter mat (EU class F8-9, MERV 14–16).…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate either that the length of time used, 6 min, was not long enough to observe any differences or that the time is excessive and short times are effective. Previous findings have found that mechanical filtration of air can reduce a swine virus (PRRSV) up to 98% (Wenke et al 2017). In this study, ozone applied at 1.8 ppm for 6 min at 80% relative humidity was able to reduce PhiX174 infectious ratios down 99.3% of its original infectious ratio.…”
Section: Rh (%) Time (Min)mentioning
confidence: 72%
“…The treatment of swine building air may reduce the risk of disease transmission within units. Mechanical and electrostatic filters treating recirculating air from swine buildings were demonstrated to effectively reduce total particles, bacteria, and airborne PRRSV (Dee et al 2010;Dee et al 2006;Lau et al 1996; Wenke et al 2017). The high particle load of swine building air requires the use of prefilters to screen larger particles before fine filters and this can increase the maintenance cost to replace or clean the fine filters and prefilters, advocating for the development of low cost and minimal maintenance infectious agents control methods.…”
Section: Introductionmentioning
confidence: 99%